CATALYTIC ACTIVITY OF CALCIUM OXIDE FROM FISHBONE WASTE IN WASTE COOKING OIL TRANSESTERIFICATION PROCESS (Jurnal Bahan Alam Terbarukan, 2017)
Calcium oxide was obtained from waste fish bones that has been carried out systematically by decomposition at various temperatures that 800oC, 900oC and 1000oC for 4 hours. Calcium oxide from the decomposition process was characterized using XRD, FTIR, SEM EDX and SAA. The result of XRD Diffractogram showed that the crystallinity increased as the calcination temperature increased. The absorption bands in the FTIR spectra of calcium oxide from calcined waste fish bones shown at 355 cm-1 region indicated Ca–O vibration, which was reinforced by the emergence of a peak at 859 cm-1. Based on the analysis using SEM EDX, the calcined waste fish bones typically irregular particles and contained dominant calcium element. The low value of BET surface area and the total of pore volume were consistent with the adsorption measurement with SAA. The calcium oxide was applied for biodiesel synthesis from Waste cooking oil through transesterification reaction. The result of the optimization that the calcium oxide was decomposed from waste fish bones at 900oC. It exhibited best catalytic activity in the transesterification of waste cooking oil providing maximum biodiesel yield of 93% at 4% (w/v) of catalyst loading. The decomposition of biodiesel are determined by GC MS that produced methyl palmitate, methyl linoleate, methyl elaidate, methyl linoleolate, methyl stearate and methyl linolenate.